Emory's gift - Cameron, W. Bruce (Forge, 2011)
In 1974, when thirteen-year-old Charlie Hall's mother dies and his father retreats into silent grief, Charlie finds himself drifting, nearly friendless, through a northern Idaho junior high school but when a grizzly bear saves his life, Charlie forms an unusual friendship that changes his life.